State Judicial Campaigns
The tape contains the recording of the second panel discussing the future of the U.S. Supreme Court. Topics covered: the state judicial systems, the relationship between elected judges and special interest groups and other campaign contributors, the spending on judicial campaigns, and the impact the 2004 election spending may have on the administration of justice. The panelists included: Bert Brandenburg (Acting Executive Director, Justice at Stake Campaign), Jan Baran (Attorney), Deborah Goldberg (Director, New York University), and Samantha Sanchez (Senior Research Fellow, Institute on Money in State Politics).